Degradation of bifenthrin and pirimiphos-methyl residues in stored wheat grains (Triticum aestivum L.) by ozonation. (15th July 2016) - Savi, Geovana D.; Piacentini, Karim C.; Bortolotto, Tiago; Scussel, Vildes M.
Highlights: The effectiveness of O3 gas treatment on the degradation of residual insecticides was evaluated. The bifenthrin residues were significantly decreased only after 180 min of O3 gas exposure. The pirimiphos-methyl residues significantly decreased in the wheat grains up to 71% for 30 min of O3 gas exposure. The presence of water (in terms of humidity) in the grains enhances the O3 degradation effect. By-products of pirimiphos-methyl with different molecular mass to charge ratios were identified by LC–MS. Abstract: Pesticide insecticides are used on wheat grains in storage units but their efficiency is hindered by persistent residues in the grains. Therefore, this study aims to evaluate the effectiveness of ozone (O3 ) gas treatment on the degradation of residual bifenthrin and pirimiphos-methyl insecticides commonly used in storage wheat grains, as well as to evaluate degradation of their by-products. The residues of bifenthrin decreased after 180 min of exposure in a concentration of 60 μmol/mol (a 37.5 ± 7.4% reduction) with 20% moisture content and 0.9 water activity. On the other hand, under the same experimental conditions, the pirimiphos-methyl residues significantly decreased in the wheat grains (71.1 ± 8.6%) after 30 min of exposure. After O3 gas treatment, three by-products of pirimiphos-methyl ( m / z  = 306.1) containing different molecular mass to charge ratios ( m / z  = 278.1, 301.1 and 319.2) were identified by LC–MS. O3 is a strong oxidizer that has shown the potential to reduce pesticide residues in stored grain in order to ensure food quality and safety.